A practical approach to securing IoT. Issue 1 (January 2019) - Perez, Gabe
Abstract : The Internet of Things (IoT) is here. A recent Gartner report states that organisations are beginning to see tremendous value in adopting IoT technology, such as revenue growth, cost reduction and monetising customer data through the delivery of value-added services. 1 Additionally, technology is advancing at a pace that makes deploying IoT resources somewhat easy.